2020
DOI: 10.1007/s00572-020-00984-6
|View full text |Cite
|
Sign up to set email alerts
|

Native forests but not agroforestry systems preserve arbuscular mycorrhizal fungal species richness in southern Ethiopia

Abstract: The rapid conversion of native forests to farmland in Ethiopia, the cradle of biodiversity, threatens the diversity of the arbuscular mycorrhizal fungi (AMF) pivotal to plant nutrition and carbon sequestration. This study aimed to investigate the impact of this land-use change on the AMF species composition and diversity in southern Ethiopia. Soil samples were collected from nine plots in each of three land-use types: native forest, agroforestry, and khat monocropping. The plots of the three land-use types wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 60 publications
7
16
0
3
Order By: Relevance
“…Delelegn et al (2017) and Birhane et al (2020), on the contrary, reported a significant reduction of AMF SA. According to Belay et al (2020) findings, while a significant reduction in AMF SA and morphospecies richness was recorded due to natural forest conversion into Agroforestry, they recorded no significant change in the case of natural forest conversion to a monoculture perennial shrub cultivation. Hence, owing to contrasting findings regarding the AMF resilience to DAF degradation and deforestation and considering the frequent high AMF resilience to tropical forests degradation and deforestation reported from elsewhere (Carrillo‐Saucedo et al, 2018; Johnson & Wedin, 1997; Picone, 2000; Stürmer & Siqueira, 2011; Violi et al, 2008; Zangaro et al, 2013; Zhang et al, 2004), additional AMF resilience studies of DAF degradation and deforestation are merited.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Delelegn et al (2017) and Birhane et al (2020), on the contrary, reported a significant reduction of AMF SA. According to Belay et al (2020) findings, while a significant reduction in AMF SA and morphospecies richness was recorded due to natural forest conversion into Agroforestry, they recorded no significant change in the case of natural forest conversion to a monoculture perennial shrub cultivation. Hence, owing to contrasting findings regarding the AMF resilience to DAF degradation and deforestation and considering the frequent high AMF resilience to tropical forests degradation and deforestation reported from elsewhere (Carrillo‐Saucedo et al, 2018; Johnson & Wedin, 1997; Picone, 2000; Stürmer & Siqueira, 2011; Violi et al, 2008; Zangaro et al, 2013; Zhang et al, 2004), additional AMF resilience studies of DAF degradation and deforestation are merited.…”
Section: Introductionmentioning
confidence: 95%
“…In the past, Lemenih et al (2005) and Tesfaye et al (2016) have studied the effects of DAF degradation and deforestation on the soil physicochemical property. Delelegn et al (2017), Birhane et al (2018, 2020), and Belay et al (2020), on‐the‐other‐hand, investigated the soil physicochemical property and AMF resilience to the degradation and deforestation of DAF. These studies reported a similar and significant reduction in soil organic carbon and total nitrogen due to DAF degradation and deforestation.…”
Section: Introductionmentioning
confidence: 99%
“…Clay soil is thought to be a suitable condition for the development of Glomus spores. Belay et al (2020) stated that clay fractions dominated native forest plots, 37 morphotypes belonging to 12 genera of Glomeromycota were found and dominated by members of Acaulospora and Glomus. In comparison, soil in the rhizosphere of pine roots was found to have the least diversity, dominated by Glomus (Figure 3).…”
Section: Density and Genus Of Arbuscular Mycorrhizal Fungi In Soilsmentioning
confidence: 99%
“…The AMF carry out key ecological activities for the operation and management of natural and agricultural systems (Davison et al, 2020;Belay et al, 2020), contributing to plant development, nutrition, and health (Ismail et al 2013;Giovannini et al, 2020;Jaitieng et al, 2020). The best performance of mycorrhizal plants is related to its higher efficiency in water and nutrient absorption (Andrade et al, 2009;Püschel et al 2020) and to improvements in this association in soil quality (Zhang et al, 2017).…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…The most diversified management of coffee plants in agroforestry systems and native forests increases the diversity of AMF (Dobo et al, 2018;Prates Júnior et al, 2019;Belay et al, 2020). This is related, among others, to the AMF enhancing the soil physical-chemical and biological properties, with better exploitation of ecological interactions.…”
Section: Introduction and Objectivesmentioning
confidence: 99%